PENGARUH KEPEMILIKAN KELUARGA TERHADAP PROFITABILITAS PERUSAHAAN PADA PERUSAHAAN MENGGUNAKAN FIRM SIZE, FIRM AGE DAN SALES GROWTH SEBAGAI VARIABEL KONTROL - Stephenly Tonggano; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This research aimed to find out whether the presence of the family in management have a positive impact on the performance of the company. The family-owned company has certain advantages compared to non family company should have better performance. One of the advantages family company have is decrease in the risk of agency problem, has strong motivation in running the company, has investment decision for the long term, more carefully in running the company, etc. This research uses ROA as the dependent variabel and Family ownership as the independent variable, besides that this research also used three control variables: firm size, firm age, sales growth. This research used 9 sector listed in IDX( Indonesia stock exchange) consist total of 533 sample company with a span of observation from 2012-2015 year observation, which in that year Indonesia experienced a slowdown of economic growth. The research results showed that family ownership had significant negative influence on ROA. Firm size had no influence on profitability of the company. Sales growth had significant negative impact in profitability and firm age had significant positive influence on company profitability.